The Role of Principal Leadership in Improving Teacher Performance - Setiawati, Lilis; Arif Wijaya, Hansein; Jamilah, Jamilah; Riyanto, Muklis; Elce Purwandari (ZAHRA: Research and Tought Elementary School of Islam Journal, 2024)
This research aims to investigate the role of the school principal's leadership in improving teacher performance at SD Negeri 3 Lubuklinggau. The research method employed is qualitative. The research subjects include the school principal, teachers, and educational staff. Data collection techniques used are interviews, observations, and documentation. The research findings reveal that the role of the school principal's leadership in enhancing teacher performance consists of providing motivation, guidance, discipline, maintaining neat appearance, offering consultations, giving recognition, conducting classroom visits, demonstrating attitudes, setting exemplary behavior, fostering active, creative, cohesive work, and developing the teaching profession. Meanwhile, the teacher performance is already quite good, as several indicators have been maximally implemented. These indicators include lesson planning, managing learning activities, establishing interpersonal relationships, conducting research, following up on assessment results, and mastering academic studies. Consequently, it can be concluded that the role of the school principal's leadership at SD Negeri 3 Lubuklinggau in enhancing teacher performance contributes positively to the advancement of learning quality, thereby promoting educational quality where the performance of educational staff is one of the keys to success in education.